ChemInform Abstract: Lewis Acid Template‐Catalyzed Asymmetric Diels—Alder Reaction. Issue 28 (25th June 2015) - Ishihara, Jun; Nakadachi, Shino; Watanabe, Yuki; Hatakeyama, Susumi
Abstract An enantioselective Diels—Alder reaction of 2, 4‐dienols and methyl acrylate is developed using a chiral Zn(II)/Mg(II) octahydro‐BINOL complex as catalytic system.